THE EFFECT OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION MODEL ON THE SOCIAL LITERACY OF PRIMARY SCHOOL STUDENTS - Yusrizal Yusrizal; Fatmawati Fatmawati; Fira Astika Wanhar (SENSEI RESEARCH CENTER, 2023)
This research was motivated by the low social literacy of students in elementary schools. Therefore, this research aims to find a new paradigm in creating learning that is able to increase students' social literacy in elementary schools. Specifically, this research aims to analyze the effect of using the Cooperative Integrated Reading and Composition (CIRC) learning model on the social literacy of elementary school students. This research design uses quasi-experiment, namely comparing the CIRC learning model with conventional learning models. This research was conducted at PAB 27 Tanjung Mulia Private Elementary School. The sample used was 48 class V students, each of which was 23 class V/a students who were designated as the experimental class and 25 class V/b students who were designated as the control class. Data collection uses tests of student literacy skills which are prepared in the form of narrative questions. The hypothesis was tested using the independent sample t test. The results of the research show that there is a significant effect of using the CIRC model on the social literacy of elementary school students. With a significant value of 0.000 and a Mean Difference value of 10.17.